Pro-Contra Of Marriage Age Restriction In Maqashid Syari’ah Perspective - Rifki Julian Wiranda; Akhmad Khisni (Law Development Journal, 2021)
Efforts to prevent marriages that are considered underage are stated in the revision of the Marriage Law (UUP) in Act No. 16 of 2019 which equates the marriage age limit for men and women to nineteen years. The purpose of the research in this article is to find out how to limit the age of marriage and the suitability of the principle of benefit of the revision of the UUP in the review of Maqashid Syari’ah. The method used in this study is a normative juridical approach and empirical data as a complement. The results showed that the practice of marriage which was considered underage occurred because the community believed that a child who entered the age of puberty should be immediately married, because it was feared that it would cause widespread damage, such as masturbation, adultery or in other forms, namely phone sex.